The pitfalls of external dependence: Greece, 1829-2015 - Carmen M. Reinhart; Christoph Trebesch (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2015)
Two centuries of Greek debt crises highlight the pitfalls of relying on external financing. Since its independence in 1829, the Greek government has defaulted four times on its external creditors - with striking historical parallels. Each crisis is preceded by a period of heavy borrowing from foreign private creditors. As repayment difficulties arise, foreign governments step in, help to repay the private creditors, and demand budget cuts and adjustment programs as a condition for the official bailout loans. Political interference from abroad mounts and a prolonged episode of debt overhang and financial autarky follows. We conclude that these cycles of external debt and dependence are a perennial theme of Greek history, as well as in other countries that have been "addicted" to foreign savings.
urn:nbn:de:bvb:19-epub-26562-1
Keywords: F3; G01; H6; N10; N13; N14; 330; Internationale Staatsschulden; Staatsbankrott; Wirtschaftsgeschichte; Griechenland